2016
DOI: 10.2147/ijn.s101141
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of mesenchymal stem cells for MRI with single-cell sensitivity

Abstract: Sensitive cell detection by magnetic resonance imaging (MRI) is an important tool for the development of cell therapies. However, clinically approved contrast agents that allow single-cell detection are currently not available. Therefore, we compared very small iron oxide nanoparticles (VSOP) and new multicore carboxymethyl dextran-coated iron oxide nanoparticles (multicore particles, MCP) designed by our department for magnetic particle imaging (MPI) with discontinued Resovist ® regardi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 77 publications
2
36
1
Order By: Relevance
“…We found that the decay in signal is correlated to the number of labeled cells, and that the scan parameters were sensitive enough to visualize about 175 labeled cells. There are published studies that reported different limits of sensitivity of detection for lower number of cells; 19,38 however, we cannot compare their findings to ours due to any of the following factors: different magnetic field strength of MRI scanners, varying MRI sequence protocols, distinct cell types, different nanoparticle formulations, and postprocessing of images. For in vivo live imaging of mice brains, we did not use the same scan sequence protocols we used for phantoms due to long scan times which were not suitable for live animals.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We found that the decay in signal is correlated to the number of labeled cells, and that the scan parameters were sensitive enough to visualize about 175 labeled cells. There are published studies that reported different limits of sensitivity of detection for lower number of cells; 19,38 however, we cannot compare their findings to ours due to any of the following factors: different magnetic field strength of MRI scanners, varying MRI sequence protocols, distinct cell types, different nanoparticle formulations, and postprocessing of images. For in vivo live imaging of mice brains, we did not use the same scan sequence protocols we used for phantoms due to long scan times which were not suitable for live animals.…”
Section: Discussioncontrasting
confidence: 66%
“…17 Iron oxide superparamagnetic nanoparticle formulations are considered as simple and effective contrast agents for MRI applications. 18 Such formulations exhibit strong negative contrast properties in both T 2 and T 2 *weighted MRI images, 19 and allow the histochemical detection of labeled cells by simple staining techniques. However, the iron oxide nanoparticle formulations and cell labeling protocols should be designed in a way to avoid any toxic effects or alteration of biological properties or functions of cells.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is reflected in the SD at each cell concentration. The resolution of MRI cell detection depends on many factors such as the r 2 value of the CA, the amount of internalized nanomaterial per cell, the MRI protocol, scanner specifications, and has reached the point of single-cell detection using Fe x O y -based nanoparticle labels [73]. The limit of cell detection with the core-shell Fe-Fe x O y NWs was not elucidated in our experimental setup.…”
Section: Magnetic Resonance Imaging Of Nanowires Internalized In Breamentioning
confidence: 94%
“…16 The higher photon-to-heat conversion efficiency of GNS, which can be tuned to have spectral absorption in the near-infrared region where tissue absorbs least, makes GNS superior in biological imaging and nanotherapeutic capabilities as compared to other commonly used nanoparticles. 14,15,[17][18][19] With regard to in vivo translation, GNS can easily penetrate tumor vasculature via EPR effect that originates from the inherently leaky tumor vasculature. 20,21 Furthermore, once delivered to the tumor microenvironment, there is minimal clearance of nanoparticles that range from 10 to 100 nm in size due to lack of an efficient lymphatic system.…”
Section: Crawford Et Almentioning
confidence: 99%